Pengembangan Produk Agribisnis Unggulan Berbasis Kearifan Lokal Di Desa Batuputih Laok Kecamata Batuputih Kabupaten Sumenep - Ribut Santosa; Purwati Ratna Wahyuni; Amir Hamzah; Bambang Hermanto (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service aims to develop superior agribusiness products based on local wisdom in Batuputih Laok Village, Batuputih Subdistrict, Sumenep Regency. The implementation method includes five main stages: needs identification and analysis, program and action plan development, training and counseling, program implementation, and monitoring, evaluation, and follow-up. The results show a significant increase in agricultural productivity and quality due to the integration of modern agricultural technology with local knowledge. Corn productivity increased by 30%, and the quality of tobacco produced improved, leading to higher selling prices. Support from the government, research institutions, the private sector, and active community participation were key factors in the program's success. In conclusion, this program successfully improved farmers' welfare and strengthened the village's agribusiness capacity sustainably.